The Unique Medicinal Properties of the Lavender Plant (International Journal of Scientific Trends, 2024)
Information is provided about the unique chemical composition of lavender, a medicinal plant belonging to the Lamiaceae family, its importance in the body, its properties in improving the nervous system, its unique properties in preventing insomnia, its antimicrobial properties, its relationship to the digestive system, and its harmful effects.